Distinct functions of two olfactory marker protein genes derived from teleost-specific whole genome duplication. (December 2015) - Suzuki, Hikoyu; Nikaido, Masato; Hagino-Yamagishi, Kimiko; Okada, Norihiro
Abstract Background Whole genome duplications (WGDs) have been proposed to have made a significant impact on vertebrate evolution. Two rounds of WGD (1R and 2R) occurred in the common ancestor of Gnathostomata and Cyclostomata, followed by the third-round WGD (3R) in a common ancestor of all modern teleosts. The 3R-derived paralogs are good models for understanding the evolution of genes after WGD, which have the potential to facilitate phenotypic diversification. However, the recent studies of 3R-derived paralogs tend to be based onin silico analyses. Here we analyzed the paralogs encoding teleost olfactory marker protein (OMP), which was shown to be specifically expressed in mature olfactory sensory neurons and is expected to be involved in olfactory transduction. Results Our genome database search identified twoOMP s (OMP1 andOMP2 ) in teleosts, whereas only one was present in other vertebrates. Phylogenetic and synteny analyses suggested thatOMP1 and2 were derived from 3R. BothOMP s showed distinct expression patterns in zebrafish;OMP1 was expressed in the deep layer of the olfactory epithelium (OE), which is consistent with previous studies of mice and zebrafish, whereasOMP2 was sporadically expressed in the superficial layer. Interestingly, OMP2 was expressed in a very restricted region of the retina as well as in the OE. In addition, the analysis of transcriptome data of spotted gar, a non-teleost fish, revealed that singleOMP gene was expressed in the eyes. Conclusion We found distinct expression patterns of zebrafishOMP1 and2 at the tissue and cellular level. These differences in expression patterns may be explained by subfunctionalization as the model of molecular evolution. Namely, singleOMP gene was speculated to be originally expressed in the OE and the eyes in the common ancestor of all Osteichthyes (bony fish including tetrapods). Then, twoOMP gene paralogs derived from 3R-WGD reduced and specialized the expression patterns. This study provides a good example for analyzing a functional subdivision of the teleost OE and eyes as revealed by 3R-derived paralogs ofOMP s.